Analysis of UMKM Promotion Strategy to Increase Sales at Sibolga Square Culinary Center Sibolga City - Masyuli Manullang, Sri; Rahmadani, Rahmadani; Hasanah Pulungan, Putri; Nasser Hasibuan, Abdul (Proceedings of International Conference on Islamic Economic Finance and Social Finance (ISSN: XXXX-XXXX) (ESSN: XXXX-XXXX), 2025)
This research was conducted on micro, small and medium enterprises at the Sibolga Square Culinary Center, Sibolga City, the purpose of the research was to find out the promotion strategy of micro, small and medium enterprises at the Sibolga Square Culinary Center, Sibolga City. The research carried out is a descriptive qualitative approach with explanations and information that will be associated with theories that will be discussed in qualitative research and provide conclusions from this research. The subjects of this study were UMKM at the Sibolga Square Culinary Center, Sibolga City. The data collection techniques used are literature study, observation, interviews and documentation, the data sources used are primary and secondary data, and data analysis consists of inductive techniques, deductive techniques and drawing conclusions. The results obtained regarding the promotion strategy of micro, small and medium enterprises at the Sibolga Square Culinary Center, Sibolga City using the concept of a promotional mix including the application of personal selling strategies (Personal Selling.